RILIEVO E VISUALIZZAZIONE 3D DI DATI DIAGNOSTICI CON STRUMENTI OPEN SOURCE IL CASO DELLA TOMBA DELLA SCIMMIA A CHIUSI - Giancristofaro, Cristina; Marras, Luciano; Palleschi, Vincenzo (Archeomatica, 2014)
This paper aims to demonstrate the usefulness of digital reconstructions in the visualization and interpretation of analytical data obtained in science conservation projects. The study was carried out in the Tomb of the Monkey, one of the most important tomb of the Etruscan necropolis of Poggio Renzo, near Chiusi, dated around 480-470 BC. Photogrammetry survey method was used to generate a 3D model of the whole underground grave. The main advantage of this method, which is based on dense stereo matching tools, is the possibility to generate 3D reconstruction starting from a set of uncalibrated images, with non invasive and easy transportable hardware. Open source software is also used to integrate 3D wall painting data to the diagnostic researches: (I) Multispectral analysis, able to improve the readability of the painted scenes, detecting details otherwise invisible to the human eye, and (II) X-Ray Fluorescence data that give information on the elemental composition of materials and confirms the behavior of the multispectral signals collected on the wall painting surfaces.